2015
DOI: 10.1371/journal.pone.0134346
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Bladder Cancer Patient-Derived Xenografts for Molecularly Guided Targeted Therapy

Abstract: BackgroundThe overarching goal of this project is to establish a patient-derived bladder cancer xenograft (PDX) platform, annotated with deep sequencing and patient clinical information, to accelerate the development of new treatment options for bladder cancer patients. Herein, we describe the creation, initial characterization and use of the platform for this purpose.Methods and FindingsTwenty-two PDXs with annotated clinical information were established from uncultured unselected clinical bladder cancer spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 51 publications
9
88
0
2
Order By: Relevance
“…We developed a diagnostic microdosing protocol to identify resistance to gemcitabine for use in a mouse model of human bladder cancer. We established four patient-derived tumor xenograft (PDX) mouse models from randomly selected myoinvasive bladder cancer patient volunteers using previously described protocols for nod scid gamma severe combined immune deficient (NSG) mice (26). These models were named BL0269 (TM00015), BL0293 (TM00016), BL0440 (TM00024) and BL0645 (TM01339), where the BL number is the UC Davis Comprehensive Cancer Center Biorepository number (http://www.ucdmc.ucdavis.edu/cancer/research/sharedresources/specimen.html) and the TM number is the Jackson Laboratory PDX database identifier (http://tumor.informatics.jax.org/mtbwi/pdxSearch.do).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed a diagnostic microdosing protocol to identify resistance to gemcitabine for use in a mouse model of human bladder cancer. We established four patient-derived tumor xenograft (PDX) mouse models from randomly selected myoinvasive bladder cancer patient volunteers using previously described protocols for nod scid gamma severe combined immune deficient (NSG) mice (26). These models were named BL0269 (TM00015), BL0293 (TM00016), BL0440 (TM00024) and BL0645 (TM01339), where the BL number is the UC Davis Comprehensive Cancer Center Biorepository number (http://www.ucdmc.ucdavis.edu/cancer/research/sharedresources/specimen.html) and the TM number is the Jackson Laboratory PDX database identifier (http://tumor.informatics.jax.org/mtbwi/pdxSearch.do).…”
Section: Resultsmentioning
confidence: 99%
“…Targeted sequencing data (whole-exome or JAX Cancer Treatment Profile) for each of the PDX (26) were filtered for 184 known DNA repair genes, including those found to correlate with response to neoadjuvant chemotherapy (NAC), such as ATM , FANCC , RB1 , BRCA1 , BRCA2 , ERCC1 , ERCC2 , and RAD51C (SI Table 5 and SI Table 6) (3, 36-39). A total of 112 somatic variants were identified in the four PDX models (SI Table 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, she had moved to her first independent position in the California Northstate School of Pharmacy, but we still continued to collaborate, recently publishing a paper together on the effects of microRNAs in bladder cancer (Vinall et al 2016). Collaboration with Dr Pan, the medical oncologist who had conducted a clinical trial based on my 2008 study also yielded a publication on the utility of patient-derived xenografts (PDX) on individualized therapy in bladder cancer patients (Pan et al 2015). These collaborations all taught me something new, something important, and something I would not have otherwise learned.…”
Section: Still Learningmentioning
confidence: 99%
“…To date, there is a limited number of established bladder cancer PDX models [4] that are molecularly characterized and available for testing drug resistance and sensitivity. Recent high throughput genomic studies have revealed several gene and pathway alterations associated with MIBC [5, 6], including PI3K/AKT/mTOR and ERK/MEK/RAS pathways as drivers of bladder cancer progression and potential targets for therapeutic interventions [3].…”
Section: Introductionmentioning
confidence: 99%